ln(2^-x+3^-x+4^-x)
可以看作是复合函数
y=ln(a),y'(a)=1/a
a=b+c+d,a'(b)=1,a'(c)=1,a'(d)=1,
b=2^e,b'(e)=ln(2)2^e,
e=-x,e'(x)=-1,
后面c,d类似,
然后根据复合函数求导就可以出结果了.
y'(x)
=(-2^-x ㏑(2) - 3^-x ㏑(3) - 4^-x ㏑g(4))/(2^-x + 3^-x + 4^-x)
y=ln[2^(-x)+3^(-x)+4^(-x)]
y'=ln'[2^(-x)+3^(-x)+4^(-x)]
={1/[2^(-x)+3^(-x)+4^(-x)]}*[2^(-x)+3^(-x)+4^(-x)]'
={1/[2^(-x)+3^(-x)+4^(-x)]}*[2^(-x)ln2*(-x)'+3^(-x)ln3*(-x)'+4^(-x)*ln4*(-x)']
={1/[2^(-x)+3^(-x)+4^(-x)]}*[-2^(-x)ln2-3^(-x)ln3-4^(-x)*ln4]
={1/[2^(-x)+3^(-x)+4^(-x)]}*[-2^(-x)ln2-3^(-x)ln3-4^(-x)*ln4]
=-{1/[2^(-x)+3^(-x)+4^(-x)]}*[2^(-x)ln2+3^(-x)ln3+4^(-x)*ln4]